DOI: 10.22215/etd/2019-13408
|View full text |Cite
|
Sign up to set email alerts
|

Preference and performance of Hypena opulenta on Vincetoxicum rossicum foliage from sun versus shade habitats

Abstract: Characteristics of individual plants from the same species can differ significantly between habitats based on abiotic factors such as light intensity and temperature. In turn, these differences in plant quality can affect herbivores that feed on the plant. Here, we examined the effects of habitat on leaf characteristics for the invasive vine Vincetoxicum rossicum, as well as the preference and performance of its biological control agent, Hypena opulenta, on sun versus shade foliage. V. rossicum leaves grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…In the United States, H. opulenta has been annually released since 2017 (Connecticut, Massachusetts, Michigan, New York, Rhode Island), but establishment has yet to be reported for these release sites or additional Canadian sites (Alred 2021;Alred et al 2022b;Livingstone et al 2020b; LRM, personal observation). Although larvae will feed nocturnally on V. rossicum in high-light (meadow) environments in which they are released, they appear to prefer the shaded conditions of low-light (forest understory) habitats (Livingstone et al 2020b;Rochette 2019). A field cage study showed that H. opulenta defoliation of V. nigrum was higher in a shaded environment, relative to a sunny environment, but the low levels of defoliation did not reduce V. nigrum fitness in either environment (Alred et al 2022b).…”
Section: Biologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, H. opulenta has been annually released since 2017 (Connecticut, Massachusetts, Michigan, New York, Rhode Island), but establishment has yet to be reported for these release sites or additional Canadian sites (Alred 2021;Alred et al 2022b;Livingstone et al 2020b; LRM, personal observation). Although larvae will feed nocturnally on V. rossicum in high-light (meadow) environments in which they are released, they appear to prefer the shaded conditions of low-light (forest understory) habitats (Livingstone et al 2020b;Rochette 2019). A field cage study showed that H. opulenta defoliation of V. nigrum was higher in a shaded environment, relative to a sunny environment, but the low levels of defoliation did not reduce V. nigrum fitness in either environment (Alred et al 2022b).…”
Section: Biologicalmentioning
confidence: 99%
“…Vincetoxicum rossicum is found in a variety of environments, but generally achieves higher survival, growth, and reproduction under high light (see "Habitat"; "Reproduction: Seed Production and Dispersal"; Hotchkiss et al 2008;Milbrath 2008;Milbrath et al 2017). Ambient light levels help determine specific leaf area in V. rossicum (Rochette 2019;Yasui 2016). Smith et al (2006) reported that V. rossicum plants grown under low light exhibited a classic shade phenotype (taller, thicker stems and larger, thinner leaves) that resulted in an increased tendency to climb over nearby plants.…”
Section: Ecophysiologymentioning
confidence: 99%